Bear - Down, Mike, 1940- ([Mahwah, N.J.] : Troll Associates, 1994)
Describes the physical characteristics, habits, and life cycle of the brown bear.
Includes index.
Keywords: Brown bear -- Juvenile literature; Bears -- Juvenile literature; Brown bear; Bears